RI 4466 Concentration Of Oxide Manganese Ores From Columbia And Elberta Mining Districts, Tooele And Juab Counties, Utah (Wildcat, Sharp, And Aeronaut No. 1 Properties) - K. C. Dean (The National Institute for Occupational Safety and Health (NIOSH), 1949)
During the investigation of the occurrence of manganese deposits in western United States, the Bureau of Mines collected 2-ton samples from three oxide manganese ores in the Columbia and Elberta Mining Districts, Tooelo and Juab Counties, Utah. To determine the amenability of these ores to standard ore-dressing methods: of concentration, extensive laboratory tests were made. The Wildcat property, one of those sampled, is 7 miles east of Fairfield, Tooele County, Utah. The ore is described as a replacement deposit and occurs along fracture and bedding planes of shale and limestone. Experimental work was done on a sample taken from a stockpile at the mouth of the shaft. The Wildcat manganese ore is intermediate in grade (25.7 percent manganese) and contains clay as the principal gangue constituent. A high-grade product was obtained with high recovery of Manganese by simple washing.